Characterization of a porcine model for associating liver partition and portal vein ligation for a staged hepatectomy. Issue 12 (December 2015) - Croome, Kristopher P.; Mao, Shennen A.; Glorioso, Jaime M.; Krishna, Murli; Nyberg, Scott L.; Nagorney, David M.
Abstract: Background: Publications using the ALPPS (associating liver partition and portal vein ligation for a staged hepatectomy) procedure have demonstrated a future liver remnant growth of 40–160% in only 6–9 days. The present study aimed to develop and describe the first large animal model of ALPPS that can be used for future studies. Methods: A total of 13 female domestic pigs underwent ALPPS stage 1 (portal vein division and parenchymal transection) followed by ALPPS stage 2 (completion left‐extended hepatectomy) 7 days later. An abdominal computed tomography (CT) scan was performed immediately prior to ALPPS stage 1 surgery and again 7 days later to assess hypertrophy immediately prior to ALPPS stage 2 surgery. Blood samples, as well as tissue analysis for Ki‐67, were performed. Results: On CT volumetric analysis, the mean size of the future liver remnant (FLR) prior to ALPPS stage 1 was 21 ± 2% and 40 ± 6% prior to ALPPS stage 2. The median degree of growth was 75% with a mean kinetic growth rate of 11% per day. Liver weights at autopsy correlated well with CT volumetric analysis ( r  = 0.87). There was no significant difference in mean lab values [asparate aminotransferase (AST), alanine aminotransferase (ALT), ammonia, International Normalized Ratio (INR) or bilirubin] from baseline until immediately prior to ALPPS stage 2. Post ALPPS stage 2 there was a significant increase in INR from baseline 1.1 to 1.6 ( P = 0.012). No post‐operative deaths secondary to liver failure were observed. Conclusion: The present study describes the first reproducible large animal model of the ALPPS procedure. The degree of liver growth and the kinetic rate of growth were similar to that which has been demonstrated in human publications. This model will be valuable as future laboratory studies are performed.